Introducción Número Especial: OUTLIERS OF PRESIDENTIAL APPROVAL: DYNAMICS, LEVELS, AND RATES - Carlin, Ryan E.; Martínez-Gallardo, Cecilia (Revista Latinoamericana de Opinión Pública, 2019)
Presidential approval tends to exhibit the dynamics of honeymoon, decline, and a rebound as elections near. But several presidential administrations and, indeed, some countries themselves, do not conform to this pattern. This introduction to the special issue identifies and classifies outliers to the typical dynamics of approval using a 12-category taxonomy and data on 140 presidential administrations in 18 Latin American countries from the Executive Approval Project 1.0. Contributors to this special issue use this taxonomy to select outlier cases to explain in their respective articles. This combination of cross-national and case-study approaches suggest a more general theory of presidential approval can be constructed by systematically testing new hypotheses generated in this special issue concerning the role of governing style, political communication, security, policy choice, and institutional context.